1996
DOI: 10.1074/jbc.271.43.26684
|View full text |Cite
|
Sign up to set email alerts
|

Novel Type of Receptor-like Protein Kinase from a Higher Plant (Catharanthus roseus)

Abstract: We characterize CrRLK1, a novel type of receptor-like kinase (RLK), from the plant Catharanthus roseus (Madagascar periwinkle). The protein (90.2 kDa) deduced from the complete genomic and cDNA sequences is a RLK by predicting a N-terminal signal peptide, a large extracytoplasmic domain, a membrane-spanning hydrophobic region followed by a transfer-stop signal, and a C-terminal cytoplasmic protein kinase with all 11 conserved subdomains. It is a novel RLK type because the predicted extracytoplasmic region shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…For instance, the MBP-XA21K K m for ATP (0.3 M) is comparable with the values obtained for the epidermal growth factor receptor (0.2-3 M), the Catharanthus roseus CrRLK1 (2-2.5 M), and the Arabidopsis RLK5 kinases (15.2-17.8 M) (19,21). Similar to CrRLK1 and the Arabidopsis BRI1 kinases, the activity of XA21K requires Mn 2ϩ and Mg 2ϩ but not Ca 2ϩ (21,22). These results suggest that autophosphorylation of XA21K may be an important step in the XA21-mediated signaling.…”
Section: Xa21k Is a Functional Kinase-to Test The Hypothesis Thatsupporting
confidence: 61%
“…For instance, the MBP-XA21K K m for ATP (0.3 M) is comparable with the values obtained for the epidermal growth factor receptor (0.2-3 M), the Catharanthus roseus CrRLK1 (2-2.5 M), and the Arabidopsis RLK5 kinases (15.2-17.8 M) (19,21). Similar to CrRLK1 and the Arabidopsis BRI1 kinases, the activity of XA21K requires Mn 2ϩ and Mg 2ϩ but not Ca 2ϩ (21,22). These results suggest that autophosphorylation of XA21K may be an important step in the XA21-mediated signaling.…”
Section: Xa21k Is a Functional Kinase-to Test The Hypothesis Thatsupporting
confidence: 61%
“…The kinase domains of SRK (8,30) and several other RLKs (38)(39)(40)(41) have been shown to possess serine͞threonine kinase activity when expressed as soluble polypeptides in E. coli. Currently, the only exception among the plant RLK family is PRK1, a pollen-specific RLK from Petunia inflata, which has been shown to autophosphorylate on serine and tyrosine residues (42).…”
Section: Discussionmentioning
confidence: 99%
“…Two methods have been employed to study the mechanism of autophosphorylation in plant receptor kinases: incubation of active and mutant KDs with different molecular mass vector tags to allow differentiation by SDS-PAGE and examination of reaction order with respect to enzyme concentration. By using one or the other of these methods, it was shown that RLK4 (Coello et al, 1999), RLK5 , and OsTMK (van der Knaap et al, 1999) followed intermolecular autophosphorylation, whereas CrRLK1 exhibited intramolecular autophosphorylation (Schulze-Muth et al, 1996). We employed both methods to show that BRI1-KD, like CrRLK1, followed an intramolecular autophosphorylation mechanism.…”
Section: Features Of the Putative Substrate Phosphorylation Sitementioning
confidence: 99%
“…Pairwise alignment of BRI1-KD with other receptor-like kinases did not reveal any obvious motif that would predict whether the kinases autophosphorylated primarily on Ser or Thr. For example, based on BLASTP alignment scores and sequence identity, CrRLK1 (Schulze-Muth et al, 1996) and TMK1 (Chang et al, 1992), which autophosphorylate predominantly on Thr, were as closely related to BRI1 as RLK5 and CLV1 (Stone et al, 1998), both of which have a preference for Ser. Nor was the type of extracellular domain any predictor of Ser versus Thr autophosphorylation, with both Leu-rich repeat and S locus-type glycoprotein domains occurring in receptor-like kinases that preferred either Ser or Thr.…”
Section: Bri1 Encodes An Active Ser/thr Kinasementioning
confidence: 99%
See 1 more Smart Citation